Electronic structure and effective masses in strained silicon - Bouhassoune, Mohammed; Schindlmayr, Arno (Physica Status Solidi C)
The structural and electronic properties of strained silicon are investigated quantitatively with ab initio computational methods. For this purpose we combine densityfunctional theory within the local‐density approximation and the GW approximation for the electronic self‐energy. From the variation of the total energy as a function of applied strain we obtain the elastic constants, Poisson ratios and related structural parameters, taking a possible internal relaxation fully into account. For biaxial tensile strain in the (001) and (111) planes we then investigate the effects on the electronic band structure. These strain configurations occur in epitaxial silicon films grown on SiGe templates along different crystallographic directions. The tetragonal deformation resulting from (001) strain induces a valley splitting that removes the sixfold degeneracy of the conduction‐band minimum. Furthermore, strain in any direction causes the band structure to warp. We present quantitative results for the electron effective mass, derived from the curvature of the conduction band, as a function of strain and discuss the implications for the mobility of the charge carriers. The inclusion of proper self‐energy corrections within the GW approximation in our work not only yields band gaps in much better agreement with experimental measurements than the localdensity approximation, but also predicts slightly larger electron effective masses.

Dynamics of photoexcitation and stimulated optical emission in conjugated polymers: A multiscale quantum-chemistry and Maxwell-Bloch-equations approach - Schumacher, Stefan; Galbraith, Ian; Ruseckas, Arvydas; Turnbull, Graham A.; Samuel, Ifor D. W. (Physical Review B)

Do we know the band gap of lithium niobate? - Thierfelder, Christian; Sanna, Simone; Schindlmayr, Arno; Schmidt, Wolf Gero (Physica Status Solidi C)
Given the vast range of lithium niobate (LiNbO3) applications, the knowledge about its electronic and optical properties is surprisingly limited. The direct band gap of 3.7 eV for the ferroelectric phase – frequently cited in the literature – is concluded from optical experiments. Recent theoretical investigations show that the electronic band‐structure and optical properties are very sensitive to quasiparticle and electron‐hole attraction effects, which were included using the GW approximation for the electron self‐energy and the Bethe‐Salpeter equation respectively, both based on a model screening function. The calculated fundamental gap was found to be at least 1 eV larger than the experimental value. To resolve this discrepancy we performed first‐principles GW calculations for lithium niobate using the full‐potential linearized augmented plane‐wave (FLAPW) method. Thereby we use the parameter‐free random phase approximation for a realistic description of the nonlocal and energydependent screening. This leads to a band gap of about 4.7 (4.2) eV for ferro(para)‐electric lithium niobate.

Ab initiog-tensor calculation for paramagnetic surface states: hydrogen adsorption at Si surfaces - Gerstmann, Uwe; Rohrmüller, M.; Mauri, F.; Schmidt, Wolf Gero (physica status solidi (c))

Optical anisotropy of Si(111)-(4 × 1)/(8 × 2)-In nanowires calculated fromfirst-principles - Wippermann, S.; Schmidt, Wolf Gero; Bechstedt, F.; Chandola, S.; Hinrichs, K.; Gensch, M.; Esser, N.; Fleischer, K.; McGilp, J. F. (physica status solidi (c))

Manganese-hydrogen complexes inGa1−xMnxN - Bihler, C.; Gerstmann, Uwe; Hoeb, M.; Graf, T.; Gjukic, M.; Schmidt, Wolf Gero; Stutzmann, M.; Brandt, M. S. (Physical Review B)

Catalytic Action of a Cu(111) Surface on Tetraazaperopyrene Polymerization - Blankenburg, S.; Rauls, E.; Schmidt, Wolf Gero (The Journal of Physical Chemistry Letters)

Entropy Explains Metal-Insulator Transition of the Si(111)-In Nanowire Array - Wippermann, S.; Schmidt, Wolf Gero (Physical Review Letters)

Defects in carbon implanted silicon calculated by classical potentials and first-principles methods - Zirkelbach, F.; Stritzker, B.; Nordlund, K.; Lindner, J. K. N.; Schmidt, Wolf Gero; Rauls, E. (Physical Review B)

First-principles investigation of CO adsorption on Pt/Ge(001)-(4×2) - Krivosheeva, A.V.; Sanna, S.; Schmidt, Wolf Gero (Computational Materials Science)

Understanding the cubic AlN growth plane from first principles - Rauls, E.; Wiebe, J.; Schmidt, Wolf Gero (Journal of Crystal Growth)

Metal-insulator transition in Si(111)-(4 × 1)/(8 × 2)-In studied by optical spectroscopy - Speiser, E.; Chandola, S.; Hinrichs, K.; Gensch, M.; Cobet, C.; Wippermann, S.; Schmidt, Wolf Gero; Bechstedt, F.; Richter, W.; Fleischer, K.; McGilp, J. F.; Esser, N. (physica status solidi (b))

First-principles study of water adsorption and a high-density interfacial ice structure on(1×1)-O/Rh(111) - Thierfelder, C.; Schmidt, Wolf Gero (Physical Review B)

Lithium niobateX-cut,Y-cut, andZ-cut surfaces fromab initiotheory - Sanna, Simone; Schmidt, Wolf Gero (Physical Review B)

GaN/LiNbO3 (0001) interface formation calculated from first-principles - Sanna, Simone; Schmidt, Wolf Gero (Applied Surface Science)

Magnetic characterization of conductance electrons in GaN - Scholle, A.; Greulich-Weber, S.; As, Donat Josef; Mietze, Ch.; Son, N. T.; Hemmingsson, C.; Monemar, B.; Janzén, E.; Gerstmann, Uwe; Sanna, S.; Rauls, E.; Schmidt, Wolf Gero (physica status solidi (b))

Chemical reactivity on surfaces: Modeling the imide synthesis from DATP and PTCDA on Au(111) - Rauls, E.; Blankenburg, S.; Schmidt, Wolf Gero (Physical Review B)

Fine Structure of Triplet Centers in Room Temperature Irradiated 6H-SiC - Scholle, Andreas; Greulich-Weber, Siegmund; Rauls, Eva; Schmidt, Wolf Gero; Gerstmann, Uwe (Materials Science Forum)
In non-annealed 6H-SiC samples that were electron irradiated at room temperature, a new EPR signal due to a S=1 defect center with exceptionally large zero-field splitting (D = +652•10-4 cm-1) has been observed under illumination. A positive sign of D demonstrates that the spin-orbit contribution to the zero-field splitting exceeds by far that of the spin-spin interaction. A principal axis of the fine structure tilted by 59° against the crystal c-axis as well as the exceptionally high zero-field splitting D can be qualitatively understood by the occurrence of additional close-lying defect levels in defect clusters resulting in comparatively large second-order spin-orbit coup¬ling. A tentative assignment to vacancy clusters is supported by the observed annealing behavior.

GaN growth on LiNbO3 (0001) - a first-principles simulation - Sanna, Simone; Schmidt, Wolf Gero (physica status solidi (c))

Temperature dependent stability of self-assembled molecular rows - Blankenburg, S.; Schmidt, Wolf Gero (physica status solidi (c))